2019
DOI: 10.1021/acsami.9b10848
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Atomic Layer Deposition of Nanostructured Gold Near Room Temperature

Abstract: A plasma-enhanced atomic layer deposition (PE-ALD) process to deposit metallic gold is reported, using the previously reported Me 3 Au(PMe 3) precursor with H 2 plasma as the reactant. The process has a deposition window from 50 to 120°C with a growth rate of 0.030 ± 0.002 nm per cycle on gold seed layers, and it shows saturating behavior for both the precursor and reactant exposure. X-ray photoelectron spectroscopy measurements show that the gold films deposited at 120°C are of higher purity than the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…A home-built pump type ALD reactor, with a base pressure of 2x10 -6 mbar, is used to carry out all atomic layer depositions, unless stated otherwise. 3 The Me 3 AuPMe 3 precursor (≥95% purity) is synthesised via the method used by Griffiths et al 1 The (CD 3 ) 3 Au(PMe 3 ) precursor (≥95% purity, and >99% deuteration) is synthesised as described in the paper of Shaw and Tobias. 10 The purity of the precursor liquids is verified by NMR measurements (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A home-built pump type ALD reactor, with a base pressure of 2x10 -6 mbar, is used to carry out all atomic layer depositions, unless stated otherwise. 3 The Me 3 AuPMe 3 precursor (≥95% purity) is synthesised via the method used by Griffiths et al 1 The (CD 3 ) 3 Au(PMe 3 ) precursor (≥95% purity, and >99% deuteration) is synthesised as described in the paper of Shaw and Tobias. 10 The purity of the precursor liquids is verified by NMR measurements (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…This is reflected by the existence of only three gold ALD processes. [1][2][3] In contrast there exists a large list of CVD processes using several different types of gold complexes to deposit gold films. 4 In this paper we will focus on the recently introduced ALD processes that make use of trimethylphosphinotrimethylgold(III) (Me 3 AuPMe 3 ) as the gold precursor which has been used as a CVD precursor before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More advanced mode matching at those three critical points will ultimately reduce the reflection and therefore improve the performance of our MMI-based circuit. For instance, the reflection due to the plasmonic waveguide could be better controlled by a more precise deposition technique such as the atomic layer deposition of gold that furthermore results in an increased Raman response [27]. Another way to improve the architecture is to engineer the MMI so that it acts as a wavelength division multiplexer [28,29] transmitting the excitation beam from a port 1 to 3 with a high transmission and transmitting it inefficiently from port 3 to port 2 while the scattered Raman light is collected in port 3.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Several studies have tested cellular responses to nanoscale topographic substrates, showing that the contact of different human tissues with nanostructured substrates can influence cellular responses in biomedical applications [ 1 , 2 , 3 , 4 ]. Studies performed to date have reported that various nanostructured substrates can modulate the adhesion and proliferation of different mammalian cell types [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%